'A Satanic spirit of pride and audacious impiety': The Grafting of the Pulcian Strain and the Politics of Poetic Style in Regency England*. (2nd January 2016) - Vassallo, Peter
Abstract : This essay focuses on adaptations of Pulci's Morgante Maggiore in early nineteenth-century England (particularly by Merivale and Frere) and Byron's appropriation of the Pulcian strain which he found so congenial to his new poetic 'Caravaggio' style, especially in some of the early Cantos of Don Juan and throughout The Vision of Judgment . It also discusses Byron's concern to redress the imbalance of Southey's sycophantic poem about George III's apotheosis, and present the case from the Whig point of view while, at the same time, defending himself against Southey's charge of his having committed an 'act of treason on English poetry'. The Pulcian style, this paper argues, contributed to Byron's crusade against the 'moral and political cant' of his day.